Influence of cognitive abilities on literacy skills in a Korean–Japanese bilingual child with developmental dyslexia - Sambai, Ami; Ju, Yeongsil; Uno, Akira (Frontiers in Psychology, 2022)
Some individuals with developmental dyslexia show dissociation in reading skills between languages. The occurrence of dissociation depends on differences in the orthographic characteristics and cognitive demands of languages. This article reports on a Korean–Japanese bilingual and biliterate boy, SJ, with developmental dyslexia (aged 11 years), who displayed dissociation between Korean and Japanese in reading and writing accuracy. This study aimed to discuss possible accounts for the profile of his literacy skills from orthographic and cognitive perspectives. To accomplish this aim, we measured SJ’s literacy skills, receptive vocabulary, and cognitive abilities (i.e., phonological skills, naming speed, and visual skills) in both Korean and Japanese. Then, we compared his skills to those of monolingual and bilingual children. In terms of accuracy, his reading skills in Korean did not differ significantly from those of bilinguals, although they were lower than Korean monolinguals. His spelling skills were within the average range for Korean monolinguals and bilinguals. In contrast, his reading and writing accuracy levels in Japanese were low compared to both Japanese monolinguals and bilinguals. Moreover, his reading and writing deficits were more remarkable in Japanese kanji. However, his cognitive profile was similar between languages. Specifically, he showed deficits in phonological skills and naming speed in both languages, as well as deficits in visual skills. These results were explained by the facts that visual skills are one of the significant predictors of reading and writing accuracy in Japanese but not in Korean, and that visual skills are a key in learning kanji. Thus, our case, SJ, supports the cognitive account, namely, the idea that different cognitive demands on the development of literacy skills can cause dissociation in literacy skills (especially in terms of accuracy) in bilingual children.